PENGARUH PERAN WARGA PEDULI AIDS TERHADAP PERILAKU DISKRIMINATIF PADA ODHA - Wati, Novi Sulistia; Cahyo, Kusyogo; Indraswari, Ratih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
The number of HIV cases in Semarang City was increased from 453 cases in 2014 to 456 cases in 2015. One of the reason why HIV cases was hard to decreased is because the persistence of stigma and discrimination to PLWHA. Warga Peduli AIDS (WPA) is manifestation of community participation to control HIV/AIDS cases that has a crucial role in reducing stigma and discrimination in PLWHA. This research aimed to analyze the effect of WPA’s role to PLWHA discrimination. This research is a quantitativewith cross sectional approach. By using purposive sampling, the samples of this research taken as many as 44 members of WPA Peterongan. The data was collected by interview using a questionnaire. This research use univariate, bivariate, and multivariate analysis.All the respondents are women. Most respondents are in the age range 41-60 years (63,6%), educated (57%), have a job (71%), and have joined the WPA for 8 years (59%). A small portion of respondents still have PLWHA discrimination (22,7%). The chi square test showed that knowledge of stigma and discrimination (p=0,002), attitude to PLWHA discrimination (p=0,0001), access to HIV/AIDS education (p=0,002), and access to VCT (p=0,023) are significantly related to PLWHA discrimination. While the variables of age (p=0,642), education (p=0,144), occupation (p=0,695), duration of joining WPA (p=1,000), and support from WPA working group (p=0,120) are not significantly related to PLWHA discrimination. The logistic regression test showed that from all variables, only attitudeabout PLWHA discrimination was influencing PLWHA discrimination (OR=20,693).